First report of melanophoroma in Salvator merianae - de Freitas, Sofia Silva La Rocca; de Paula Pereira, Lucas; da Silva, Maria Estela Mendes [UNESP]; Chinen, Karina Harumi; Bandarra, Márcio de Barros (Brazilian Journal of Veterinary Pathology, 2024)
Cutaneous neoplasms have been described in the class Reptilia, and many of them are related to the inadequate management of these animals in captivity. In Brazil, there are few reports of cutaneous neoplasms in Iguana iguana, but no reported cases in Salvator merianae. Therefore, the objective of this work was to report a case of a melanophoroma diagnosed in a Salvator me-rianae. A tegu with a skin nodule located in the dorsal region, close to the right scapula, measuring 1 cm, in diameter, blackish, elevated, firm in consistency, well defined, non-ulcerated and non-adherent, was surgically removed and sent to histopathology analysis, witch revel melanophoroma. The animal in this report had a follow up for eight months after the procedure, and was discharged without signs of other skin nodules. The present report seeks to add to the literature on reptile medicine by describ-ing a histopathological diagnosis of melanophoroma in Salvator merianae, in addition to the clinical-surgical treatment and its respective clinical follow-up.
Keywords: chromatophoromas; cutaneous neoplasms; reptiles